ICASSP 2019 - 2019 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2019
DOI: 10.1109/icassp.2019.8682793
|View full text |Cite
|
Sign up to set email alerts
|

Muse-ing on the Impact of Utterance Ordering on Crowdsourced Emotion Annotations

Abstract: Emotion recognition algorithms rely on data annotated with high quality labels. However, emotion expression and perception are inherently subjective. There is generally not a single annotation that can be unambiguously declared "correct." As a result, annotations are colored by the manner in which they were collected. In this paper, we conduct crowdsourcing experiments to investigate this impact on both the annotations themselves and on the performance of these algorithms. We focus on one critical question: th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…Especially for frequent videogame players, who have personal experiences with the dynamics of shooter games, this video is easier to interpret and the affective high-points are easier to recognise. This is also supported by a recent study of Jaiswal et al [40], who also observed an effect between the context of the annotation task and the quality of labels.…”
Section: Resultssupporting
confidence: 82%
“…Especially for frequent videogame players, who have personal experiences with the dynamics of shooter games, this video is easier to interpret and the affective high-points are easier to recognise. This is also supported by a recent study of Jaiswal et al [40], who also observed an effect between the context of the annotation task and the quality of labels.…”
Section: Resultssupporting
confidence: 82%
“…We use four common emotion recognition datasets: MSP-Improv (Busso et al 2017), MSP-Podcast (Lotfian and Busso 2017), Interactive Emotional Dyadic MOtion Capture (IEMOCAP) dataset (Busso et al 2008), and Multimodal Stressed Emotion (MuSE) dataset (Jaiswal et al 2019).…”
Section: Datasetsmentioning
confidence: 99%
“…We use three datasets to study the effect of stress on emotion recognition: (1) Multimodal Stressed Emotion (MuSE) dataset [19]; (2) Interactive Emotional Dyadic MOtion Capture (IEMOCAP) dataset [6]; and (3) MSP-Improv dataset [7].…”
Section: Datasetsmentioning
confidence: 99%
“…Emotion Labels. Each utterance in the MuSE dataset was labeled for activation and valence on a nine-point Likert scale by eight crowd-sourced annotators [19], who observed the data in random order across subjects. We average the annotations to obtain a mean score for each utterance, and then bin the mean score into one of three classes, defined as, {"low": [min, 4.5], "mid": (4.5, 5.5], "high": (5.5, max]}.…”
Section: Labelsmentioning
confidence: 99%